A plant design on the coconut wet process using solvol method - San Juan, Bayani (College of Engineering, 1978)
Plant: coco-oil, coco-protein, coco-flour -- Location: Southern Tagalog Region -- Annual capacity at maximum rate of production: coconuts (with husks) 130,000 kg., N-Hexane 20,722 kg., coco-oil 29,593, coco-protein 4,102.8, coco-flour 7,018.9, coco-husk 28,900, coco-shell 20,020 -- Fixed capital investments: 23,994,418 -- Annual manufacturing cost at maximum capacity: 44,724,773 -- Working days: 300 days/yr. -- Break-even point: 62.4% -- Shut/down point: 40.4% -- Pay-out time: 2.9 yrs.